Re-establishing Impact Speed Requirements for Inducing Commotio cordis - Grant James Dickey; Sakib Ul Islam; Kewei Bian; Haojie Mao (CMBES Proceedings, 2023)
INTRODUCTION Commotio cordis (CC) is a sudden death mechanism involving pump failure of the heart from impacts over or near the cardiac silhouette [1] and has garnered heavy publicity due to the sporting incidences involving American football player Damar Hamlin and ice hockey player Chris Pronger. While these events took place 25 years apart, they are both unique in the sense that CC occurred in 2 professional athletes with discrete impacts to the heart. It has been established that CC requires low-velocity impacts to the chest ranging from 30 to 50-mph [2]. This study investigated the re-establishment of impact speed requirements to induce CC with older age groups and developed bodies of adults. METHODS This study administered the Total Human Model for Safety (THUMS), a finite element model of an adult male, to recreate CC inducing impacts. An anonymous survival case of CC involving a 19-year-old male collegiate baseball player was reconstructed and analyzed. Based on recollections and witness analysis, the player was struck directly over the heart with a 90-mph pitch and was not wearing a chest protector. To further understand what was happening to the heart during this impact, we used the AM50 (Adult male 50th percentile) model with a regulation sized baseball aimed directly over the heart at speeds of 90-mph. Left ventricular strain values from impact were measured. RESULTS Strain dispersion seen throughout the adult heart showed large portions of the left ventricle experiencing strain levels upwards of 25%. Approximately 40% of the left ventricular tissue was engulfed in these strain levels (Fig. 1). Left ventricular strain was highest in the epicardium of the left ventricle, suggesting that the electrically disturbed cardiac tissue would likely be found in this region. Fig. 1 Comparison of AM50 heart during 90-mph baseball impact (left) and 10-year-old heart during 40-mph baseball impact (right), showing peak strain values of the left ventricular region of the heart. DISCUSSION Currently, the established requirements for inducing CC state the impact speed must be in the range of 30 to 50-mph. When comparing the strain values from the AM50 model with 90-mph impacts to previous studies using a child 10-year-old model [3] with 40-mph impacts, we can see that the strain levels and distribution are strikingly similar (Fig. 1). This study provides evidence that CC impact speeds of 30 to 50-mph may be specific only to youth, and as individuals get older with a larger and stiffer thoracic cavity, the impact speed requirements for CC increase with age. Therefore, CC is reliant on age, weight, and stiffness of the individual, and should be seen as a spectrum regarding induction impact speeds, rather than absolute values. This is an important case analysis supporting re-establishing of the required speeds for inducing CC, and should influence chest protector design and regulations across all sports regarding the prevention of CC. REFERENCES J. Maron et al., "Clinical profile and spectrum of commotio cordis," (in eng), JAMA, vol. 287, no. 9, pp. 1142-6, Mar 2002. S. Link et al., "An experimental model of sudden death due to low-energy chest-wall impact (commotio cordis)," New England Journal of Medicine, vol. 338, no. 25, pp. 1805-1811, 1998. J. Dickey et al. “Identifying Vulnerable Impact Locations to Reduce the Occurrence of Deadly Commotio Cordis Events in Children’s Baseball: A Computational Approach,” J Biomech Eng. Vol. 144, no. 5, May 01 2022.